An empirical relationship between company growth and the market price of securities listed on the Johannesburg Stock Exchange - Narendra Bhana (South African Journal of Business Management, 1992)
There appears to be a widespread belief among investors that growth companies and growth stocks are identical. The objective in this article is to determine if the shares of high growth companies listed on the Johannesburg Stock Exchange (JSE) provided superior investment returns during the period 1974-88. The empirical evidence revealed that high growth companies underperform because the market overestimates their future growth and future return on equity, as a result their shares tended to have overvalued price-earnings ratios. Therefore, the investor will incur substantial losses if their results are below expectations. It is hypothesized that a cognitive bias may be responsible for the erroneous identification of growth stocks as shares of growth companies. Company results have a tendency to regress to the mean as the underlying economic forces attract new entrants to attractive markets and leave low-growth businesses. Because of this tendency, companies that have provided high growth in the past may prove to be inferior future investments. Past financial attributes cannot be relied upon to predict future returns. The investor should integrate a rigorous valuation model into the share selection procedure so that estimates of future growth and profitability can be used to make an estimate of expected returns.Dit blyk dat daar 'n algemene mening onder beleggers bestaan dat groeiende maatskappye en groeiende effekte een en dieselfde is. Die doel van hierdie ondersoek is om te bepaal of die aandele van maatskappye wat op die Johannesburgse Effektebeurs genoteer word en wat 'n hoe groei toon, hoer opbrengste gelewer het gedurende die tydperk 1974-88. Die empiriese bevindings dui daarop dat hoegroeimaatskappye onderpresteer, omrede beleggers hul toekomstige groei en toekomstige opbrengste oorskat, met die gevolg dat hul aandele oorgewaardeerde prysverdienste-verhoudings toon. As gevolg hiervan strek dit tot nadeel van die belegger as die uitslae nie aan die verwagtings voldoen nie. Die hipotese word gemaak dat 'n bewussynsvooroordeel moontlik daarvoor verantwoordelik is dat groei-aandele foutiewelik as aandele van groeiende maatskappye geindentifiseer word. Maatskappy-uitslae het die neiging om terug te keer tot die gemiddelde, na gelang die onderliggende ekonomiese kragte nuwe deelnemers na aantreklike markte lok, weg van laegroeimarkte. As gevolg van die neiging mag maatskappye wat in die verlede hoe groei getoon het, swak toekomstige beleggings wees. Daar kan dus nie op voormalige finansiele kenmerke vertrou word om toekomstige opbrengste te voorspel nie. Die belegger behoort 'n streng skattingsmodel in sy keuse van effekte te integreer sodat skattings van toekomstige groei en winsgewendheid gebruik kan word om 'n skatting van verwagte opbrengste te maak.
Keywords: 650